2015
DOI: 10.1093/gbe/evv026
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomics of Phrynosomatid Lizards: Conflicting Signals from Sequence Capture versus Restriction Site Associated DNA Sequencing

Abstract: Sequence capture and restriction site associated DNA sequencing (RADseq) are popular methods for obtaining large numbers of loci for phylogenetic analysis. These methods are typically used to collect data at different evolutionary timescales; sequence capture is primarily used for obtaining conserved loci, whereas RADseq is designed for discovering single nucleotide polymorphisms (SNPs) suitable for population genetic or phylogeographic analyses. Phylogenetic questions that span both “recent” and “deep” timesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
145
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(161 citation statements)
references
References 66 publications
12
145
2
2
Order By: Relevance
“…thynnus branch is supported by 3 analyses only when lowering the BV to 80% (Table 1). As reported by other studies (Cruaud et al, 2014;Hipp et al, 2014;Hou et al, 2015;Jones et al, 2013;Leaché et al, 2015;Rubin et al, 2012;Wagner et al, 2013), the use of IUPAC encoded sites and allowing higher missing data percentages not only produces larger matrices, but also results in better resolved trees (Table 1). Yet, although high bootstrap alone is not evidence of tree accuracy (Rodríguez-Ezpeleta et al, 2007), the congruence obtained among our different analyses is considered a good indicator of true evolutionary signal in the data (Hillis, 1995;Rubin et al, 2012).…”
Section: Phylogeny Of the Genus Thunnussupporting
confidence: 67%
See 1 more Smart Citation
“…thynnus branch is supported by 3 analyses only when lowering the BV to 80% (Table 1). As reported by other studies (Cruaud et al, 2014;Hipp et al, 2014;Hou et al, 2015;Jones et al, 2013;Leaché et al, 2015;Rubin et al, 2012;Wagner et al, 2013), the use of IUPAC encoded sites and allowing higher missing data percentages not only produces larger matrices, but also results in better resolved trees (Table 1). Yet, although high bootstrap alone is not evidence of tree accuracy (Rodríguez-Ezpeleta et al, 2007), the congruence obtained among our different analyses is considered a good indicator of true evolutionary signal in the data (Hillis, 1995;Rubin et al, 2012).…”
Section: Phylogeny Of the Genus Thunnussupporting
confidence: 67%
“…Cruaud et al, 2014;Herrera and Shank, 2015;Leaché et al, 2015). Yet some studies have shown that gathering a suitable set of phylogenetically informative markers from RAD-seq data relies on the ability to discover enough orthologous loci among the species under study, which largely depends on divergence times between lineages and filtering and assembly parameters applied for orthology inference (Jones et al, 2013;Leaché et al, 2015;Rubin et al, 2012;Wagner et al, 2013). It is therefore recommended to explore the results applying different parameter combinations (Ree and Hipp, 2015;Rubin et al, 2012 Cells and Animal Tissue".…”
Section: Introductionmentioning
confidence: 99%
“…Instead, we prefer to wait for a study that addresses these issues by incorporating nuclear DNA (preferably RadSeq or UCE; e.g. Leaché et al 2015), additional morphological characters, and new material from potential sampling gaps. Until then, we refer to the populations representing the southern clade as Trimeresurus (Popeia) sp.…”
Section: Discussionmentioning
confidence: 99%
“…Next, the pipeline conducts multiple sequence alignments for all candidate loci using ClustalW (Larkin et al 2007), and paired AE/UCE flanking sequences are concatenated to form each individual locus. Loci found on the same chromosomes should be sufficiently separated from each other in order for their gene trees to be effectively independent of each other (Hudson and Coyne 2002;Jennings and Edwards 2005;Wakeley 2009;McCormack et al 2012;Reilly et al 2012;O'Neill et al 2013;Leaché et al 2015). Thus, the user must input a second distance threshold (in base pairs) separating sampled loci.…”
mentioning
confidence: 99%